Pengaruh Budaya Organisasi dan Motivasi terhadap Mutu Kinerja Penyaluran BPNT Kota Bekasi - Rachmat Fadly; Ananto Krisna Wardhana; Riris Lestiowati; Kurniawan Prambudi Utomo; Sinta Rukiastiandari (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The purpose of the research on the influence of organizational culture and motivation on the performance quality of the Bekasi City Non-Cash Food Assistance (BPNT) distribution is to find out how much influence the organizational culture and motivation variables have on the quality of performance, using quantitative methods, statistical data testing is carried out after obtaining primary and secondary data. secondary from respondents consisting of employees of the Social Service and Beneficiary Families (KPM) by conducting interviews, field observations (field research) with the method of distributing questionnaires directly as many as 40 respondents, while the results of this study indicate that the organizational culture variable is positive and the motivational variable is positive. low negative, so it can be concluded that organizational culture and motivation variables have a significant positive influence on the quality of the distribution performance of BPNT Bekasi City.